Fatigue life prediction of nuclear reactor main bolt based on temperature effect and size effect. (November 2021) - Li, Z.H.; Han, K.; Chen, T.; Yang, H.S.; Liu, P.; Lu, Y.H.
Highlights: Fatigue strength was evaluated based on the temperature effect and size effect. By combining the TCD, fatigue life could be efficiently evaluated. Fatigue fracture mechanism of the bolt material was analyzed. Abstract: The temperature effect and size effect on the fatigue life of nuclear reactor main bolt material were studied, and the high temperature fatigue limit of actual bolt thread was evaluated based on the temperature effect and exponential model of size effect. The results showed that the fatigue life of bolt material decreased with the increase of temperature, which exhibited obvious temperature effect. On the other hand, the size effect mainly depended on the loading stress levels because of different effects of stress level on fatigue crack initiation. When the stress level was higher than 340 MPa, fatigue crack initiation was less dependent on defects and the size effect was small, which the fatigue life of large size component could be approximately evaluated by smaller size specimen; by comparison, when the stress level was lower than 300 MPa, fatigue crack initiation was strongly dependent on defects and the size effect became obvious, and at that time the fatigue limit of different size specimen was consistent with exponential model. The fatigue limit of large size bolt under actual service temperature could be obtained by the product of size effect and temperature effect. By combining the theory of critical distance (TCD) with a series of small size fatigue test, the fatigue life of large size components could be efficiently evaluated under the premise of greatly reducing small size fatigue tests.